Laboratory Study of the Effect of Reinforcement Strips (CFRP) on the Ductility and Confinement of Reinforced Concrete Columns - Abd Al-Razaq, Amjad Hameed; Zaki, Rana Ismael Khaleel (Nahrain University College of Engineering Journal, 2017)
The issue of repairand reinforcement of structures is one of the major branches of civil engineering. In this direction, the reinforcement of the pressure members, especially the reinforced concrete columns by reinforced polymer sheetsis considered as one of the conventional methods in reinforcing these members. By confining the pressure member and preventing lateral expansion resulting from the Poisson’s effect,the FRP sheetbrings about an increase in compression strength and ductility. In this laboratory research, the effects of different methods of reinforcing concrete columns by CFRP sheets including the effect of the width of reinforcing sheets on ductility and stress-strain behavior of the concrete columns in the presence of internal reinforcement of the column were studied. The steel reinforcement of column includes evaluation of the effect of longitudinal and transverse steel bars, number of transverse bar, and also development bar of longitudinal reinforcement on the rate of confinement.The results of this research show that by suitable arrangement of CFRP reinforcing sheets, the confinement in the reinforced concrete columns can be created appropriately